The Psychiatrist–Patient Relationship within the Deinstitutionalised Context of Primary Health Care - Baltrušaitytė, Giedrė (Sociologija. Mintis ir veiksmas, 2003)
This article discusses psychiatrist–pacient relationship within the deinstitutionalised context of primary mental health care. Discussion is based on 19 semi-structured interviews with psychiatric outpatients attending mental health care services at Kaunas mental health care centres (MHCC).The interviews showed that, despite the goals and values of deinstitutionalisation, which emphasises patients’ autonomy, empowerment and socio-economic integration within society, the paternalistic model of psychiatrist – patient relationships is further reproduced within MHCC. This relationship is based on rigid hierarchical roles of a dominating psychiatrist taking traditional stance of “doctor knows better” and a passive, dependent and submissive patient. As a consequence, patients are left in a disempowering position that prevents them from taking charge of their own lives and health as well as makes their adaptation in society more difficult. Therefore, there is a need for a more empowering re-conceptualisation of a psychiatric patient.
Keywords: mental health care; psychiatrist–pacient relationship; paternalism